Determinant of labor absorption in Yogyakarta - Mohammad Dendi Abdul Nasir; Mukhamad Yazid Afandi; Hishamuddin Mohd Ali (Optimum: Jurnal Ekonomi dan Pembangunan, 2023)
This study aims to examine government expenditure, investment, economic growth and inflation and their effect on labor absorption in the Special Region of Yogyakarta (DIY) in the 2010–2019 research period and to prove the Okun’s law and Phillips curve in DIY. Methodologically, this research was conducted using quantitative methods using secondary data. The data analysis technique used is panel data analysis with the chosen approach, namely the random effect model. Based on the results of the simultaneous test, this study shows that the four independent variables together have a positive and significant influence on labor absorption in the DIY Province. Meanwhile, based on the results of the partial test, it shows that the variables of government expenditure and inflation have a positive and significant effect on labor absorption. Investment and economic growth variables have a negative and significant effect on labor absorption. Implication of the study is the importance of the effectiveness of government expenditure and investment to increase labor absorption and strengthen the environment of investment to stimulate labor absorption in DIY.